Effectiveness of corpus consultancy in teaching verb+noun collocations to first-year ELT students - Akıncı, Mehmet. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study aims to examine the effectiveness of data-driven learning (DDL), explicit instruction and combined method in teaching verb+noun (V+N) collocations to advanced Turkish learners of English through measuring these learners’ recognition accuracy of V+N collocations and their judgment about the acceptability of these collocations. It also aims to explore the opinions of these learners about corpus consultancy in learning V+N collocations. DDL-Group (D-Group) following DDL included 20, Explicit Instruction-Group (EI-Group) following explicit instruction included 19, and Combined-Group (C-Group) following both DDL and explicit instruction included 19 participants. Quantitative data were analyzed via one-way independent analysis of variance and descriptive statistics. Results revealed a statistically significant difference among three groups in their recognition accuracy of V+N collocations. While EI-Group and C-Group were significantly better than DGroup, the means of the EI-Group and C-Group did not significantly differ from each other. With respect to the judgment about the acceptability of V+N collocations, EIGroup significantly outperformed D-Group; however, the difference between EI-Group and C-Group; and C-Group and D-Group was not statistically significant. A selfevaluation questionnaire and semi-structured interviews provided the qualitative data. The questionnaire data showed that the participants found the instruction with corpus consultancy more useful and effective in learning V+N collocations than the one without corpus consultancy. Inductive content analysis of the interview data revealed that the past learning experiences of the participants could have influenced the results of the study; and the research task as well as the time of treatment given needed to be tailored for further research.
Keywords: Corpora (Linguistics); Collocation (Linguistics); English language -- Study and teaching.